1986
DOI: 10.1093/schbul/12.4.578
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Monitoring in the Rehabilitation of Schizophrenic Patients

Abstract: Although precise laboratory methods for measuring psychopathology are not available, interviewer-rated instruments developed to assess symptomatology can be used to monitor schizophrenic patients undergoing rehabilitation. By regularly assessing patients, rehabilitation staff can improve the effectiveness of their interventions. Patients can be screened for high levels of symptomatology which might preclude assignment to rehabilitation programs with high levels of social stimulation. Monitoring the prodromal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
337
0
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(340 citation statements)
references
References 31 publications
0
337
0
3
Order By: Relevance
“…Impairment Variables. We summed eight symptom constructs from the BPRS checklist (Luckoff, Liberman, and Neuchterlein 1986;Overall and Gorham 1962) to provide an interviewer assessment of clinical impairment. These were conceptual disorganization, excitement, motor retardation, blunted affect, tension, mannerisms and posturing, uncooperativeness, and emotional withdrawal.…”
Section: Instruments and Measurement Of Variablesmentioning
confidence: 99%
“…Impairment Variables. We summed eight symptom constructs from the BPRS checklist (Luckoff, Liberman, and Neuchterlein 1986;Overall and Gorham 1962) to provide an interviewer assessment of clinical impairment. These were conceptual disorganization, excitement, motor retardation, blunted affect, tension, mannerisms and posturing, uncooperativeness, and emotional withdrawal.…”
Section: Instruments and Measurement Of Variablesmentioning
confidence: 99%
“…Two scores describing negative symptoms, "affective flattening" and "cognitive impairment," were based on a principal components analysis (PCA) of all ratings from the Brief Psychiatric Rating Scale (BPRS) (Lukoff et al 1986), the Scale for the Assessment of Negative Symptoms (SANS) (Andreasen 1981), the Positive and Negative Syndrome Scale (PANSS) (Kay et al 1987), and the Psychological Impairment Rating Schedule 'Data from two control subjects were rejected, from one subject because of obvious skin potential contamination, and from another subject because of persistent large eye movements.…”
Section: Subjectsmentioning
confidence: 99%
“…Most studies point to a relationship between face affect recognition and negative symptoms, but the specificity of this relationship is still unclear. Several studies have found general face processing deficits (both affect and identity recognition) related to specific negative symptoms, such as anergia (Lukoff et al, 1986;, whereas other studies have found that facial affect recognition deficits but not face perception correlated with specific negative symptoms (e.g. alogia) (Gaebel and Wolwer 1992;Kohler eẗ al., 2000) and overall severity of negative symptoms (Baudouin et al, 2002;Schneider et al, 1995;Lewis and Garver, 1995).…”
Section: Introductionmentioning
confidence: 99%